2010
DOI: 10.1002/bit.22775
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human cytochrome P450 monooxygenases for drug metabolite synthesis

Abstract: Cytochrome P450 monooxygenases (CYPs) are important enzymes in the metabolism of xenobiotics. Therefore, several approaches to clone and overexpress the human isoforms have been made. In addition to microsomes or S9 preparations, these recombinant human isoforms have found diverse application in drug development. We discuss and give examples of the use of bacterial whole cell systems with rec. human CYPs for the preparative scale synthesis of drug metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 32 publications
0
64
0
1
Order By: Relevance
“…This progress can directly be of use for efficient and timesaving production of human drug metabolites. High yields and conversion rates can already be achieved by using corresponding human (Rushmore et al, 2000;Vail et al, 2005;Schroer et al, 2010;Geier et al, 2012;Schiffer et al, 2015) or suitable nonhuman (Taylor et al, 1999;Otey et al, 2006;Sawayama et al, 2009;Reinen et al, 2011;Di Nardo and Gilardi, 2012;Kiss et al, 2015;Ren et al, 2015) P450 enzymes in a whole-cell system to produce respective metabolites. The majority of published bacterial P450 enzymes used for the conversion of drugs are mutants of CYP102A1 (BM3) from Bacillus megaterium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This progress can directly be of use for efficient and timesaving production of human drug metabolites. High yields and conversion rates can already be achieved by using corresponding human (Rushmore et al, 2000;Vail et al, 2005;Schroer et al, 2010;Geier et al, 2012;Schiffer et al, 2015) or suitable nonhuman (Taylor et al, 1999;Otey et al, 2006;Sawayama et al, 2009;Reinen et al, 2011;Di Nardo and Gilardi, 2012;Kiss et al, 2015;Ren et al, 2015) P450 enzymes in a whole-cell system to produce respective metabolites. The majority of published bacterial P450 enzymes used for the conversion of drugs are mutants of CYP102A1 (BM3) from Bacillus megaterium.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the utilization of human P450 enzymes enables the sufficient production of human drug metabolites employing baculovirus-infected insect cells expressing CYP3A4 or CYP2D9 (Rushmore et al, 2000), fission yeast expressing CYP2D6 (Peters et al, 2007) or CYP2C9 (Drǎgan et al, 2011;Neunzig et al, 2012), and Escherichia coli cells expressing CYP3A4, CYP2C9, and CYP1A2 (Vail et al, 2005). Since it is not mandatory to employ associated human P450 enzymes to synthesize human drug metabolites (Schroer et al, 2010;Geier et al, 2015), microbial, especially bacterial, P450 enzymes serve as a good alternative because they are convenient to handle and usually hold higher expression levels and activities, recommending the possibility to employ them as useful biocatalysts (Bernhardt, 2006). The genetic manipulation of bacterial P450 enzymes toward a drug metabolizing activity has been successfully demonstrated for several P450 enzymes including the most studied P450 102A1 (BM3), CYP102A1 (Whitehouse et al, 2012;Ren et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cytochromes P450 (CYPs) (EC 1.14.14.1) are a large super family of heme-containing monooxygenases that catalyzes mostly C-H hydroxylations on a wide range of endogenous as well as exogenous compounds [48]. Many of these chemical transformations are difficult to perform through synthetic methods, and therefore are of great interest for biocatalytic applications [49].…”
Section: Exploring Complex Enzymatic Mechanisms: P450 Monooxygenase Amentioning
confidence: 99%
“…Phase I metabolism involves the introduction or exposure of a reactive polar group on the xenobiotic via oxidation, resulting in a more reactive/water soluble metabolite to facilitate excretion and/or the induction of phase II metabolism. The cytochrome p450 super family of oxidases catalyse the majority of these reactions, although other oxidases, esterases, amidases, and monooxygenases can also be involved (Schroer et al, 2010). Phase II metabolism involves the conjugation of charged species such as glutathione, sulphate, glycine or glucuronic acid to the phase I metabolite to increase its water solubility (Kohalmy and Vrzal, 2011).…”
Section: Bioactivationmentioning
confidence: 99%